Pulau Jawa Battleground, Arena Persaingan Politik Terbesar Pemilihan Umum 2024 - Junaedi, Junaedi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Java Island is the battleground, the key and the fiercest battleground between presidential and vice-presidential candidates and political parties in 2019. The latest data from the Central Statistics Agency (BPS) noted that the number of Indonesians living on the island of Java reached 154.28 million or around 56 percent of the total population in 2022 of 275.7 million. Meanwhile, of the population, the General Election Commission or KPU has determined as many as 204.8 million permanent voter lists (DPT), with a total of 56.3 percent or 115.37 are voters living on the island of Java. The Java’s centric trend why Java Island is a Battleground in the 2024 Election, this is based on the Permanent Voter List (DPT) that has been inaugurated by the General Election Commission (KPU), the number of voters on the island of Java reaches 115 million people. The portion is around 56% of the total national voters which amounted to 204.8 million people, meaning that winning in Java 85-95% will definitely be The causes of the implementation of the Presidential, Vice President, and Legislative Members are downright and dishonest and fair (Jurdil), including: 1). Circulation practices Money Politics (money politics), and the distribution of social assistance (banso) using the budget of the State Budget/APBD/BUMN/BUMDis the most worried thing for the public during the event 2024 Election; 2). Non-neutrality of state administrators, state apartments and civil servants to certain presidential/vice presidential candidates; 3). The alignment of law enforcement officials, especially the Constitutional Court, the TNI/Polri and other agencies to certain candidates.